y + 2.3 = 0.45x
y = 0.45x - 2.3
-2y = 4.2x - 7.8
-2(0.45x - 2.3) = 4.2x - 7.8
-0.90x + 4.6 = 4.2x - 7.8
-0.90x - 4.2x = -7.8 - 4.6
-5.1x = - 12.4
x = -12.4 / -5.1
x = 2.4
y + 2.3 = 0.45x
y = 0.45(2.4) - 2.3
y = 1.08 - 2.3
y = -1.2
solution is : (2.4, - 1.2)
Unfortunately, I can't do it on a graph here, but I will do it algebraically.
The solution on the graph will be the point of intersection of the two lines representing the equations.
y + 2.3 = 0.45x . . . . . (1)
-2y = 4.2x - 7.8 . . . . . (2)
From (2), y = 3.9 - 2.1x
substituting for y in (1), we have:
3.9 - 2.1x + 2.3 = 0.45x
2.55x = 6.2
x = 6.2/2.55 = 2.4
y = 3.9 - 2.1(2.4) = 3.9 - 5.04 = -1.2
Therefore, solution is (2.4, -1.2)